Study of lipid alterations related with Alzheimer disease - Melo, Tânia Sofia Rodrigues de (2012)
Alzheimer disease is characterized by defects in the signaling mediated by acetylcholine. Tacrine was used as acetylcholinesterase (AChE) inhibitor approved for the treatment of Alzheimer’s disease. However, tacrine treatment has some toxicological effects associated with mitochondrial dysfunction, ROS generation and lipid peroxidation. Deregulation in sphingolipid metabolism is also associated with establishment and progression of this disease. In this study, mass spectrometry was used to identify the membrane phospholipid profile of rats brain non-synaptic mitochondria, before and after treatment with tacrine and its analogues (samples T1 and T2). The results obtained with this study allowed us to understand that treatment with tacrine induces changes in mitochondrial phospholipid content, seems to increase the susceptibility to oxidation of mitochondrial PS, and affects mitochondrial bioenergetics. O tratamento com os análogos T1 e T2 parece induzir menores alterações nos parâmetros avaliados, quando em comparação com a tacrina. Treatment with T1 and T2 analogues seems to induce less change in evaluated parameters, comparing with tacrine. T1 analogue was shown to be the most efficient of all in its inhibitory capacity for AchE activity. This work contributes to a better understanding of the effects of tacrine in brain mitochondrial function, and to research of new tacrine analogues with more inhibitory efficiency and with lower toxicological effects. To better understand the changes in sphingolipid-induced oxidative stress, a possible process underlying Alzheimer's disease, we studied the oxidative modification of specific SM (d18:1/16:0), SPC (d18:1) and Cer (d18:1/18:0) induced by hydroxyl radical generated under conditions of Fenton reaction (H2O2 and Fe2+), using mass spectrometry. The results of this study allowed us to identify for the first time, several oxidation products produced during the oxidation of SM and SPC. This work contributes to a better understanding of the behavior of some sphingolipids under conditions of oxidative stress, important for its possible detection in biological systems.